Federalismo y Unitarismo: semejanzas y diferencias de los procesos de descentralización de Venezuela y Perú. - Quintana, Carlos Mascareño (Universidad del Rosario, 2010)
Venezuela is a country with federal roots that launched its decentralization process in 1989 with the election of governors and mayors. Peru has a constitutional basis of unitary design that, after a failed decentralization process at the end of the 80’s, returned to this path in November 2002 with the election of regional presidents. There are concurrent elemerns in both cases with regard to the building of political consensus in order to grant the legitimacy of the process, as well as certain differences in their orientations. This paper will study both realities in a comparative way, in order to draw SOIEC lessons about their merits and short comings.